2018
DOI: 10.1111/ejn.13890
|View full text |Cite
|
Sign up to set email alerts
|

Neural capacity limits during unconscious semantic processing

Abstract: A growing body of neuroimaging data suggests that direct measurements of brain activity can reveal subliminal effects that remain invisible with behavior measures alone. We examined whether sentence comprehension processes could be triggered by a sequence of masked words. On each trial, participants viewed a rapid sequence of masked or unmasked words, including a subject noun, three adverbs and followed by a visible target verb. To probe the capacity limits of unconscious processing, we measured event-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…It has proven difficult to put upper bounds on the depth of non-conscious processing. Non-conscious signals tend to affect a wide range of behaviors and trigger activity in many different brain areas, including the prefrontal cortex (27,28). Recent work on non-conscious WM has even called into question basic assumptions regarding the nature of non-conscious processes, suggesting that non-conscious stimuli may be maintained much longer than previously thought (7)(8)(9)(10)26).…”
Section: Discussionmentioning
confidence: 99%
“…It has proven difficult to put upper bounds on the depth of non-conscious processing. Non-conscious signals tend to affect a wide range of behaviors and trigger activity in many different brain areas, including the prefrontal cortex (27,28). Recent work on non-conscious WM has even called into question basic assumptions regarding the nature of non-conscious processes, suggesting that non-conscious stimuli may be maintained much longer than previously thought (7)(8)(9)(10)26).…”
Section: Discussionmentioning
confidence: 99%
“…Still, in our paradigm, single words could occur in different prime positions. Previous studies have shown that the Stimulus Onset Asynchrony (SOA) between prime and target affects the strength of semantic priming (Greenwald et al, 1996;Kiefer, 2002;Kiefer and Brendel, 2006;Nakamura et al, 2018). Therefore, we investigated whether prime position affected N400 amplitude.…”
Section: Erps: N400 Modulations By Prime Visibility and Semantic Compmentioning
confidence: 97%
“…not good), can be performed under masked processing van Gaal et al, 2014), although only after considerable training of the negation process (van Gaal et al, 2014). Some authors have suggested that masked combinatorial processing occurs for entire sentences Nakamura et al, 2018;Sklar et al, 2012), even though evidence is mixed (Rabagliati et al, 2018;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has proven notoriously difficult to put clear upper bounds on the depth of nonconscious processing. Non-conscious signals tend to affect a wide range of behaviors and trigger activity in many different brain areas, including the prefrontal cortex (van Gaal et al, 2010;Naccache and Dehaene, 2001;Nakamura et al, 2018;van Vugt et al, 2018). Recent work on non-conscious WM has even called into question some of the most basic assumptions regarding the nature of non-conscious processes, suggesting that non-conscious signals may be maintained much longer than previously thought (Bergström and Eriksson, 2017;King et al, 2016;Soto et al, 2011;Trübutschek et al, 2017).…”
Section: Manipulation As a Limit For Non-conscious Silent Processesmentioning
confidence: 99%